STUDI NUMERIK PERBANDINGAN KARAKTERISTIK ALIRAN BACKWARD FACING STEP DENGAN BODI PENGGANGGU (BUMP) TIPE RECTANGULAR DENGAN BILANGAN REYNOLDS TINGGI - Bayu Dwi Cahyo (Jurnal Penelitian)
This research uses a backward facing step geometry with additional rectangular bump on the inlet. The rectangular bump with variation mixed length (l) model developed in this study is very important for predicting fluid flow among boundary layer especially in reattachment length, the prediction obtained by applying standard wall function and non-equilibrium wall function with turbulence model RKE Realizable. Furthermore, the results are compared with previous experimental research data Kim dkk. 2005. This research is investigated using 2D simulation Computational Fluid Dynamics (CFD) with Parameter to be used are: step height (h): 1 cm; variation of mixing length (l): 5; 4; 3; and 2 cm; rectangular side (d): 0.5 cm. All investigations are running with Reynolds Number 38,000, based on the step height and the mean stream. From this study we will obtain the best combination of turbulent models and the near-wall treatment method. It also give prediction show the best reattachment length prediction in position l/h 5 from the comparison of the results of the distance variation of the body model.